Evaluación técnico- financiera de la corrida de revestimientos de 133/8”, 95/8” y 7” con la herramienta CRT (Revestimiento Running Tool) en el campo Castilla (2018)
With the aim of reducing the times associated with Coating runs during operations in Campo Castilla, Ecopetrol S.A. decided to implement the CASING RUNNING TOOL technology from Pointer Instruments LTDA, which eliminates operational problems caused by the use of conventional tools during coatings runs. This project consists of the collection, comparison and analysis of the performance data obtained during the 9 5/8 "and 13 3/8" coating runs in the Pozo Castilla 230 with the conventional tool and with the CRT tool in the Well Castilla 255. The well selection process was carried out taking into account the tool with which the lining was run and the depth of the wells. With the collected data, a series of comparisons and analyzes were generated in terms of run times, non-productive times, flat times and costs, through which the positive aspects of the implementation of the CRT tool were determined. Finally, the results are concluded and a series of recommendations are presented, for their application in future wells in Field Castilla.